The ‘face(book)-ache’ of alternative media: Probing Greek grassroots media strategies in the age of the social web - Vatikiotis, Pantelis; Milioni, Dimitra L. (My University, 2023)
The present study explores the broad alternative media realm, employing the metaphor of media ecology to address the intersection between varieties of activism and different media, and draws on the mediation paradigm to explore the appropriation of digital media by diverse alternative media producers. At the empirical level, the study evaluates the positions and tactics of Greek grassroots media in the age of the social web probing grassroots media producers’ discourses and concerns over the employment of digital technologies. It reflects on controversial issues raised in regard to the enhancement and enrichment of the media-locus of resistance in the digital era, and discusses challenges and limitations raised by the employment of corporate social media in the Greek alternative mediascape.
Keywords: activism; digital media; grassroots media; Greece; media ecology; mediation; resistance; social media